Interchanging interaction between heritage and technical in the local architectural practice - Enas Salim Abdul-Ahadd; Rana Mazin Mahdi (Iraqi Journal of Architecture and Planning, 2018)
An architectural local practice facing a crisis associated with losing the local intermediatedfeature for local heritage and rapid development, which is a feature of the current era.Theresearch focuses on the case of intermediation in expression between heritage privacy (as itcannot be denied the whole heritage or accept the whole) and the expression of the spirit ofthe times and new techniques to ensure the continuity of architectural output achieved in timeand space thus The research problem absented of equilibrium expressionist architecturaloutput arises between the ancient and the modern..Proceeding from the need Establishmentthe successes of architectural based inherited to attributes of the positive image associatedwith sense and collective memory and without verbatim copying or repeat boring of itscomponents may represent objective of this research offering mechanics to harnessdevelopments technological era to achieve the balancing expressive with local heritage toensure re-line local architectural back on track right through emphasize in their possession onelements and traditional forms of obstetric capacity for new forms stating the design processand architectural practice as a whole.To achieve the target research had to belimiteda steps which represent as:- Û±Clarify the role of the architectural heritage of the container to the external forces ofchange (represented by contemporary technology) to confront the case of alienation.- Û²highlight the technical for the development of architectural production to ensure continuityand contact with the former- Û³Recovery mechanisms to modernize and applied to the heritage elements of Baghdadheritage an elected for the application to provide alternatives to represent architecturaldesigner formal possibilities to connect with the old in a new modern kind of case the revivalof traditional elements.